Factors Impacting Differential Outcomes in the Definitive Radiation Treatment of Anal Cancer Between HIV‐Positive and HIV‐Negative Patients. (4th June 2020) - Susko, Matthew; Wang, Chia‐Ching Jackie; Lazar, Ann A.; Kim, Stephanie; Laffan, Angela; Feng, Mary; Ko, Andrew; Venook, Alan P.; Atreya, Chloe E.; Van Loon, Katherine; Anwar, Mekhail
Abstract: Background: Anal squamous cell carcinoma (ASCC) is uncommon, yet seen more frequently in the setting of the human immunodeficiency virus (HIV). Chemoradiotherapy is the definitive modality of treatment for patients with ASCC; this study examines factors impacting clinical outcomes in a large cohort of HIV‐positive and HIV‐negative patients. Methods: A retrospective review was conducted of patients treated for nonmetastatic ASCC at a single institution between 2005 and 2018. Freedom from local recurrence (FFLR), freedom from distant metastasis, and overall survival (OS) were calculated using the Kaplan‐Meier method, and univariate and multivariate analysis were performed using the Cox proportional hazards model. Results: During the study period, 111 patients initiated definitive treatment for ASCC. Median age of the entire cohort was 56.7 years (interquartile range, 51.5–63.5), with 52 patients (46.8%) being HIV‐positive. At median follow‐up of 28.0 months, the 2‐ and 5‐year FFLR were 78.2% (95% confidence interval [CI], 70.4–87.0) and 74.6% (95% CI, 65.8–84.5), respectively. Multivariate analysis revealed time from diagnosis to treatment initiation (median, 8 weeks; hazard ratio, 1.06; 95% CI, 1.03–1.10) to be significantly associated with worse FFLR and OS. HIV‐positive patients had a trend toward worse FFLR (log‐ranked p = .06). For HIV‐positive patients with post‐treatment CD4 less than 150 cells per mm 3, there was significantly worse OS (log‐ranked p = .015). Conclusion: A trend toward worse FFLR was seen in HIV‐positive patients, despite similar baseline disease characteristics as HIV‐negative patients. Worse FFLR and OS was significantly associated with increased time from diagnosis to treatment initiation. Poorer OS was seen in HIV‐positive patients with a post‐treatment CD4 count less than 150 cells per mm 3 . Implications for Practice: Human immunodeficiency virus (HIV)‐positive patients with anal squamous cell carcinoma can represent a difficult clinical scenario. Definitive radiation with concurrent chemotherapy is highly effective but can result in significant toxicity and a decrease in CD4 count that could predispose to HIV‐related complications. As HIV‐positive patients have largely been excluded from prospective clinical trials, this study seeks to provide greater understanding of their outcomes with radiation therapy, potential predictors of worse local control and overall survival, and those most at risk after completion of treatment. Abstract : This article reports on a malignancy often driven by an infectious disease that predisposes patients to its development but also complicates the treatment paradigm: anal squamous cell carcinoma (ASCC) in the HIV‐positive population. The report describes factors that most significantly affect ASCC outcomes in HIV‐positive patients and evaluates predictors of clinical outcomes of ASCC treatment among both HIV‐positive and HIV‐negative patients.